NEEDED: A GLOSSARY TO ACCOMPANY AUDIT REPORTS. - Singer, Frank A. (The Accounting Review, 1960)
Abstract A student in an elementary accounting class was asked to record the transaction in which a donation had made to the Junior League. The problem of transmitting ideas clearly and accurately is so formidable and of such long standing that it is well-known to all. There are those who believe that its genuine solution would quickly lead to the end of wars. It is important and desirable to establish a uniform terminology, but it will take a long time and one must not hope for too much. The Committee has done much constructive work toward this long-term goal, and this writer relied often upon its work in making his own recommendations with regard to the terminology problem. A precise and uniform terminology will permit the effective accomplishment of this rather necessary service. It should not be necessary to prepare a separate glossary for each report. There should be many terms which will always be present and which can be set up in a standard glossary with which the work of firm members will always be consistent.